Akuntansi Seni Jaranan Pada Masyarakat Kalibaru Dengan Pendekatan Etnografi - Sofiatur Rohmah; Siti Nor Maisyah; Nurdiana Aprilia Firdausi; Intan Maulydia Taufany; Ainun Amira (Politeknik Negeri Jember, 2023)
The research aims to depict and interpret accounting practices within the Jaranan art community and understand the accounting concept within the cultural context of Jaranan art. Cultural art is created by humans as a symbol of belief in the surrounding environment, reflecting back to the creator to follow their teachings. The Jaranan art in Kalibaru is known as Jaranan Campursari Turonggo Sakti. The author observes Jaranan art in Kalibaru as an organization and a means of livelihood for artists involved in this Jaranan art group. Data were obtained from informants (members of the Jaranan art cultural group) through in-depth interviews and documentation. The reconstruction of the accounting concept within Jaranan art indicates that the community views accounting as something that could be done merely as an imagination without undergoing the recording process, which complicates the task for administrators document it. Instead, they rely solely on values of honesty and responsibility.